ANALISIS DAYA SAING PARIWISATA KOTA MALANG - Muflih, Muhammad Fadhlan; Ananda , Candra Fajri (Journal of Development Economic and Social Studies, 2022)
The tourism industry is an important contributor to the economic success of a country. This is one of the supports in the development of tourism activities to become an important industry. Malang City interprets "Beautiful Malang" as a city that has beauty and offers tourist charms that are very attractive, fun, and comfortable to be used as tourist destinations. The purpose of this study was to determine the development of the competitiveness of the tourism sector in the city of Malang and to determine the condition of the competitiveness of the city of Malang compared to the competitiveness of other districts/cities in the Greater Malang area by using a competitiveness monitor analysis. The results show that the tourism competitiveness of Malang City on the Human Tourism Indicator (HTI), Price Competitiveness Indicator (PCI), Environment Indicator (EI), and Human Resource Indicator (HRI) indicators are good but on the Infrastructure Development Indicator (IDI), Openness indicators Indicators (OI), and Social Development Indicators (SDI) are still low.